Unexpected decrease in necrotizing enterocolitis morbidity during the COVID-19 pandemic-A single-centre retrospective study - Wang, Yu; Cui, Mingling; Li, Lili; Gao, Chuchu; Feng, Zongtai; Cai, Yan; Yang, Zuming; Shen, Lirong (Frontiers in Pediatrics, 2024)
Background: The impact of the coronavirus disease 2019 (COVID-19) pandemic on neonatal necrotizing enterocolitis (NEC) is not well characterised. This cross-sectional study evaluated the potential effects of pandemic-related measures on NEC morbidity in premature infants in a neonatal ward during the COVID-19 pandemic. Methods: This was a retrospective study conducted in a tertiary neonatal ward in eastern and central China over 6 consecutive years (2017, 2018, 2019, 2020, 2021 and 2022). The medical records of 189 premature infants with stage II or III NEC were reviewed for clinical manifestations and aetiologies. The data were analysed and compared between the prepandemic period (2017, 2018, and 2019) and the pandemic period (2020, 2021 and 2022). Results: A total of 9903 infants with gestational age (GA) < 37 weeks were enrolled, including 5382 in the prepandemic period and 4521 in the pandemic period. A reduction in stage II or III NEC morbidity was observed in infants with GA < 37 weeks, with an average annual morbidity of 2.29% (123/5382) (95%CI, 1.89%-2.68%) in the prepandemic period and 1.46% (66/4521) (95% CI, 1.11%-1.81%) in the pandemic period. NEC morbidity showed resurgent characteristics in 2021. When prepandemic coinfections were excluded, most cases of NEC with bloodstream infections in the prepandemic period were attributable to Gram-negative bacteria (27/32, 84.38%), mainly Klebsiella pneumoniae, while in the pandemic period they were attributable to Gram-positive bacteria (10/18, 55.56%), mainly Staphylococcus aureus. Antimicrobial susceptibility testing revealed that Klebsiella pneumoniae was 100% sensitive to meropenem, imipenem, ciprofloxacin and levofloxacin and 100% resistant to ampicillin. Staphylococcus capitis was 100% sensitive to vancomycin, linezolid, tetracycline, cotrimoxazole and cefoxitin and 100% resistant to penicillin and benzathine. Conclusions: COVID-19 pandemic-related interventions can reduce the morbidity of NEC and change the pathogen spectrum in patients with bloodstream infections. We need to understand the exact factors leading to these changes.